Fenomena ‘No Viral No Justice’: Dinamika Komunikasi dalam Mencari Keadilan pada Era Digital di Indonesia - Ihsan, M. Fikri; Torong, Achmad Ofanny S; Ginting, Rahmanita (Universitas Medan Area, 2025)
This study aims to examine how the “No Viral No Justice” phenomenon influences legal proceedings in the digital era in Indonesia, specifically through agenda-setting and framing mechanisms on social media. Employing a qualitative approach, the research analyzes two cases: (1) the death of a young woman named Vina in Cirebon and (2) the assault of a bakery employee by George Sugama. Data collection methods include non-participant observation and content analysis of platforms such as Twitter and TikTok. Findings reveal that the intensity of user engagement, the role of influencers, and emotional narratives constructed on social media effectively prompt a faster response from law enforcement agencies. Conversely, this phenomenon also carries the risk of trial by social media and misinformation when fact verification is neglected. In conclusion, “No Viral, No Justice” can serve as a shortcut for victims with limited legal access; however, improved digital literacy and careful legal safeguards are necessary to maintain objectivity and professionalism in law enforcement.